2018
DOI: 10.3389/fimmu.2017.01917
|View full text |Cite
|
Sign up to set email alerts
|

Intravital Microscopic Evaluation of the Effects of a CXCR2 Antagonist in a Model of Liver Ischemia Reperfusion Injury in Mice

Abstract: BackgroundIschemia–reperfusion (IR) is a major contributor to graft rejection after liver transplantation. During IR injury, an intense inflammatory process occurs in the liver. Neutrophils are considered central players in the events that lead to liver injury. CXC chemokines mediate hepatic inflammation following reperfusion. However, few studies have demonstrated in real-time the behavior of recruited neutrophils. We used confocal intravital microscopy (IVM) to image neutrophil migration in the liver and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 75 publications
5
19
0
Order By: Relevance
“…CXCL2 is also known as an essential mediator in sterile liver injury which could alter hepatic function and hepatotoxicity by regulating hepatic neutrophil accumulation . A recent study showed that treatment with reparixin, an antagonist of the CXCL2 receptor, decreased not only the recruitment of neutrophils in tissues but also their activation state in the liver which was associated with better liver function and histologic outcome in sterile liver injury . Our result showed reduced hepatic neutrophil infiltration and attenuated liver damage in CCl 4 ‐injected mice that received anti‐CXCL2 neutralizing antibody, in line with the previous reports, indicating that CXCL2 is an important mediator of sterile liver inflammation.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…CXCL2 is also known as an essential mediator in sterile liver injury which could alter hepatic function and hepatotoxicity by regulating hepatic neutrophil accumulation . A recent study showed that treatment with reparixin, an antagonist of the CXCL2 receptor, decreased not only the recruitment of neutrophils in tissues but also their activation state in the liver which was associated with better liver function and histologic outcome in sterile liver injury . Our result showed reduced hepatic neutrophil infiltration and attenuated liver damage in CCl 4 ‐injected mice that received anti‐CXCL2 neutralizing antibody, in line with the previous reports, indicating that CXCL2 is an important mediator of sterile liver inflammation.…”
Section: Discussionsupporting
confidence: 91%
“…However, the hepatic macrophages in CCl 4 ‐treated MBL −/− mice displayed a higher level of CXCL2 compared with WT counterparts. It is noteworthy that CXCL2 is a potent chemotactic and activation factor of neutrophils and plays a critical role in neutrophil recruitment during acute inflammation . CXCL2 is also known as an essential mediator in sterile liver injury which could alter hepatic function and hepatotoxicity by regulating hepatic neutrophil accumulation .…”
Section: Discussionmentioning
confidence: 99%
“…1,[5][6][7] Neutrophils comprise a substantial portion of the amplifier cell population in the initial immune response, and their involvement in IR injury is hypothesized to be, in part, due to the formation of neutrophil extracellular traps (NETs) containing web-like extrusions of nuclear DNA, citrullinated histones, and antimicrobial peptides released into the tissue by activated neutrophils. [8][9][10] NETs have been implicated in a wide variety of diseases, notably autoimmune diseases such as lupus [11][12][13] and rheumatoid arthritis. 14,15 Additionally, NETs have also been shown to form following traumatic injury both systemically and at the site of injury, [16][17][18][19][20][21] including in models of ischemic injury in vital organs.…”
Section: Introductionmentioning
confidence: 99%
“…Hepatic energy metabolism and an optimal intracellular environment rely on an adequate blood supply. Hepatocytes are very sensitive to ischemia and/or hypoxia in liver tissue[18,19]. Therefore, factors related to ischemia and/or hypoxia will definitely influence their metabolism[20].…”
Section: Discussionmentioning
confidence: 99%